2006
DOI: 10.1055/s-2006-924084
|View full text |Cite
|
Sign up to set email alerts
|

Physiological Responses of Forest Trees to Heat and Drought

Abstract: The heat wave of summer 2003 was the largest and the most persistent ever experienced in Central Europe and has fuelled concern about the effects of climate change on European ecosystems. Since forests constitute the most important European ecosystems, in this review article we assess current knowledge on the effects of heat and drought on key metabolic processes for growth and productivity of forest trees. In particular, the general consequences of heat and drought on (1) photosynthesis and respiration at the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

13
299
2
17

Year Published

2008
2008
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 415 publications
(331 citation statements)
references
References 130 publications
(134 reference statements)
13
299
2
17
Order By: Relevance
“…It has been suggested that fluctuations in temperature extremes and water deficit issue will be the key determinants of future climatic conditions. This fact has already been proved in the form of 2003 summer heat wave in Europe where an increase of 5°C above normal temperature was sustained throughout the summer period [23]. As compared to the other living organism plants being motionless have less chance to escape the stress conditions [24].…”
Section: Causes Of Climatic Variationsmentioning
confidence: 93%
“…It has been suggested that fluctuations in temperature extremes and water deficit issue will be the key determinants of future climatic conditions. This fact has already been proved in the form of 2003 summer heat wave in Europe where an increase of 5°C above normal temperature was sustained throughout the summer period [23]. As compared to the other living organism plants being motionless have less chance to escape the stress conditions [24].…”
Section: Causes Of Climatic Variationsmentioning
confidence: 93%
“…Mediterranean climate is well known for long lasting periods of drought during summer, with large irradiance loads and temperature maxima that may reach 40 to 45 • C. Such conditions impose strong stresses on leaves of tree species like oaks (Rennenberg et al, 2006). High temperatures above 40 • C, may under circumstances induce leaf necroses and yellowing (Schreiber and Berry, 1977).…”
Section: Introductionmentioning
confidence: 99%
“…As plantas também podem se utilizar de estratégias de escape de perda de água excessiva a exemplo da abscisão foliar, a qual pode ser programada ou ser desencadeada pela própria condição de deficiência hídrica (DOSMANN et al, 1999). O aumento na espessura do mesofilo é uma estratégia que pode contribuir para evitar danos fotoxidativos, cuja suscetibilidade aumenta na condição de deficiência hídrica (RENNENBERG et al, 2006). O aprofundamento das raízes para manter a absorção de água suficiente para suprir a demanda da planta é outra estratégia importante para garantia de sobrevivência a longos períodos de estiagem .…”
Section: Introductionunclassified